Contribution of Arm Muscle Strength, Eye Coordination and Level of Consertation to Volleyball Down Passing as Moderating Variables - Ramadhan Wisnu Wardana; Martinus, Martinus; Bayu Hardiyono; Arif Hidayat; Karmila Utari (UNIB Press, 2025)
The objectives of this research are as follows 1) To find out how much arm muscle strength (X1) contributes to the concentration level (Y) of students at SDN 171 Palembang; 2) To find out how much contribution Hand Eye Coordination (X2) has to the level of concentration (Y) of students at SDN 171 Palembang; 3)To find out how much the level of concentration (Y) contributes to the bottom passing of volleyball (Z) of students at SDN 171 Palembang; 4) To find out how much arm muscle strength (X1) contributes to the bottom passing of volleyball (Z) of students at SDN 171 Palembang; 5) To find out how much hand eye coordination (X2) contributes to the bottom passing of volleyball (Z) of students at SDN 171 Palembang; 6) To find out how much arm muscle strength (X1) contributes to Hand Eye Coordination (X2) of students at SDN 171 Palembang. This type of research method is quantitative research with a partial correlation approach. Quantitative methods are methods that are based on numerical information or quantities, and are usually associated with statistical analyzes. The results of the research can be concluded that there is a contribution of arm muscle strength, hand eye coordination and level of concentration to passing volleyball at SD Negeri 171 Palembang. Research suggestions for schools, teachers and parents are expected to establish good cooperation to create an atmosphere so that students can concentrate on doing anything, especially to improve students' academic and non-academic achievements in the field of sports